Confirmation of Y haplogroup tree topologies with newly suggested Y-SNPs for the C2, O2b and O3a subhaplogroups. (November 2015) - Kwon, So Yeun; Lee, Hwan Young; Lee, Eun Young; Yang, Woo Ick; Shin, Kyoung-Jin
Highlights: We investigated Y-SNPs newly suggested for the C2, O2b and O3a subhaplogroups. We observed Y haplogroup (C2, O2b and O3a haplogroups) distribution in 545 Korean males. The position of JST002613-27 marker was identified to designate C2e haplogroup rather than C2f haplogroup. The O2b1 haplogroup was defined by the F3356 marker not by the M312 marker. O2b1b was the most common haplogroup (19.0%) found in the Korean population. Abstract: Y chromosome single nucleotide polymorphisms (Y-SNPs) are useful markers for reconstructing male lineages through hierarchically arranged allelic sets known as haplogroups, and are thereby widely used in the fields such as human evolution, anthropology and forensic genetics. The Y haplogroup tree was recently revised with newly suggested Y-SNP markers for designation of several subgroups of haplogroups C2, O2b and O3a, which are predominant in Koreans. Therefore, herein we analyzed these newly suggested Y-SNPs in 545 unrelated Korean males who belong to the haplogroups C2, O2b or O3a, and investigated the reconstructed topology of the Y haplogroup tree. We were able to confirm that markers L1373, Z1338/JST002613-27, Z1300, CTS2657, Z8440 and F845 define the C2 subhaplogroups, C2b, C2e, C2e1, C2e1a, C2e1b and C2e2, respectively, and that markers F3356, L682, F11, F238/F449 and F444 define the O subhaplogroups O2b1, O2b1b, O3a1c1, O3a1c2 and O3a2c1c, respectively. Among six C2 subhaplogroups (C2b, C2e, C2e1*, C2e1a, C2e1b and C2e2), the C2e haplogroup and its subhaplogroups were found to be predominant, and among the four O2b subhaplogroups (O2b*, O2b1*, O2b1a and O2b1b), O2b1b was most frequently observed. Among the O3a subhaplogroups, O3a2c1 was predominant and it was further divided into the subhaplogroups O3a2c1a and O3a2c1c with a newly suggested marker. However, the JST002613-27 marker, which had been known to define the haplogroup C2f, was found to be an ancestral marker of the C2e haplogroup, as is the Z1338 marker. Also, the M312 marker for the O2b1 haplogroup designation was replaced by F3356, because all of the O2b1 haplotypes showed a nucleotide change at F3356, but not at M312. In addition, the F238 marker was always observed to be phylogenetically equivalent to F449, while both of the markers were assigned to the O3a1c2 haplogroup. The confirmed phylogenetic tree of this study with the newly suggested Y-SNPs could be valuable for anthropological and forensic investigations of East Asians including Koreans.